Diabetes, plasma glucose and incidence of fatty liver, cirrhosis and liver cancer: A prospective study of 0.5 million people - Pang, Y; Kartsonaki, C; Turnbull, I; Guo, Y; Clarke, R; Chen, Y; Bragg, F; Yang, L; Bian, Z; Millwood, I; Hao, J; Han, X; et al. (Wiley, 2018)
The prevalence of diabetes is increasing rapidly in China. However, evidence is limited about its effects on chronic liver diseases and liver cancer. We aimed to examine the associations of diabetes with chronic liver diseases and liver cancer and of random plasma glucose (RPG) with these liver diseases among participants without diabetes in Chinese adults, and to assess the possible interaction by hepatitis B virus (HBV) infection. The prospective China Kadoorie Biobank recruited 512,891 adults. During 10 years of follow-up, 2,568 liver cancer, 2,082 cirrhosis, 1,298 hospitalised non-alcoholic fatty liver disease (NAFLD), and 244 hospitalised alcoholic liver disease (ALD) were recorded among 503,993 participants without prior history of cancer or chronic liver diseases at baseline. Cox regression was used to estimate hazard ratios (HRs) for each disease by diabetes status (previously diagnosed or screen-detected) and, among those without previously diagnosed diabetes, by levels of RPG. Overall 5.8% of participants had diabetes at baseline. Compared with those without diabetes, individuals with diabetes had adjusted HRs of 1.49 (95% CI 1.30-1.70) for liver cancer, 1.81 (1.57-2.09) for cirrhosis, 1.76 (1.47-2.16) for NAFLD, and 2.24 (1.42-3.54) for ALD. The excess risks decreased but remained elevated in those with longer duration. Among those without previously diagnosed diabetes, RPG was positively associated with liver diseases, with adjusted HRs per 1 mmol/L higher RPG of 1.04 (1.03-1.06) for liver cancer, 1.07 (1.05-1.09) for cirrhosis, 1.07 (1.05-1.10) for NAFLD, and 1.10 (1.05-1.15) for ALD. These associations did not differ by HBV infection.In Chinese adults, diabetes and higher blood glucose levels among those without known diabetes are associated with increased risks of liver cancer and major chronic liver diseases. This article is protected by copyright. All rights reserved.